Utilization of ceramic waste as fine aggregate within Portland cement and fly ash concretes - Torkittikul P. (2014)
The aim of this research work was to investigate the feasibility of using ceramic waste and fly ash to produce mortar and concrete. Ceramic waste fragments obtained from local industry were crushed and sieved to produce fine aggregates. The measured concrete properties demonstrate that while workability was reduced with increasing ceramic waste content for Portland cement concrete and fly ash concrete, the workability of the fly ash concrete with 100% ceramic waste as fine aggregate remained sufficient, in contrast to the Portland cement control concrete with 100% ceramic waste where close to zero slump was measured. The compressive strength of ceramic waste concrete was found to increase with ceramic waste content and was optimum at 50% for the control concrete, dropping when the ceramic waste content was increased beyond 50%. This was a direct consequence of having a less workable concrete. However, the compressive strength in the fly ash concrete increased with increasing ceramic waste content up to 100%. The benefits of using ceramic waste as fine aggregate in concrete containing fly ash were therefore verified. © 2010 Elsevier Ltd. All rights reserved.